An analysis of the intersecting factors and needs that informed the experiences of young people transitioning from out of home care in the Australian states of Victoria and Western Australia. (June 2023) - Mendes, Philip; Martin, Robyn; Jasmin Jau, Ms; Jacinta Chavulak, Ms
Highlights: Preparation and planning for transitions from out of home care is often poor. Where smoother transitions occurred, they involved a combination of material supports and relationship supports producing greater ontological security. Extending the age of leaving care till at least 21 years would advance more positive outcomes. Abstract: Young people transitioning from out-of-home care (often called care leavers) are globally a disadvantaged group who can be particularly vulnerable to experiences of housing instability and homelessness. This qualitative study, based on interviews with 34 care leavers in the Australian states of Victoria and Western Australia, examined their transition experiences and outcomes with a specific focus on access to stable and affordable housing. Our study reported major deficits in transition planning including a significant reliance when leaving care on specialist homelessness services to meet housing needs. Some major policy and practice reforms were identified concerning transition planning, service coordination, and extending the leaving care age to 25 years.